2009
DOI: 10.1002/jbm.b.31500
|View full text |Cite
|
Sign up to set email alerts
|

Differences between bisphosphonates in binding affinities for hydroxyapatite

Abstract: Bisphosphonates (BPs) inhibit bone resorption and are widely used for the treatment of bone diseases, including osteoporosis. BPs are also being studied for their effects on hydroxyapatite (HAP)-containing biomaterials. There is a growing appreciation that there are hitherto unexpected differences among BPs in their mineral binding affinities that affect their pharmacological and biological properties. To study these differences, we have developed a method based on fast performance liquid chromatography using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 32 publications
4
96
0
3
Order By: Relevance
“…The maximal amount of 3a bound to HA is much higher (nearly 1.5 to 1.9 fold) than those of 3b-e because of only a small difference in the substituent R 2 . As shown in the previous study, [26] when the risedronate was attached to an extra methyl group in the R2 side chain, the two BPs had different retention times (16.16 and 14.41 respectively) indicating the decrease of HA binding affinity. As detected by a constant composition potentiostatic method, Nancollas et al demonstrated significant differences in the binding affinity of similar BPs to HA and carbonated apatite and established a rank order of ibandronate , alendronate , pamidronate.…”
Section: Crystal Structuressupporting
confidence: 50%
See 1 more Smart Citation
“…The maximal amount of 3a bound to HA is much higher (nearly 1.5 to 1.9 fold) than those of 3b-e because of only a small difference in the substituent R 2 . As shown in the previous study, [26] when the risedronate was attached to an extra methyl group in the R2 side chain, the two BPs had different retention times (16.16 and 14.41 respectively) indicating the decrease of HA binding affinity. As detected by a constant composition potentiostatic method, Nancollas et al demonstrated significant differences in the binding affinity of similar BPs to HA and carbonated apatite and established a rank order of ibandronate , alendronate , pamidronate.…”
Section: Crystal Structuressupporting
confidence: 50%
“…[7] Also, a method based on fast performance liquid chromatography (FPLC) uses columns of HA, to which BPs and other phosphate-containing compounds can adsorb and be eluted. [26] Even though these methods can qualify binding affinities, a more accurate, precise, and economic method should be developed. In the present work, to quantify the bone targeting efficiency of the BPs 3a]e, a new method was set up using HPLC which employs the most common detection system and the simplest chromatography elution conditions found in experimental and clinical laboratories.…”
Section: Crystal Structuresmentioning
confidence: 99%
“…Bisphosphonates bind to bone and prevent resorption, although binding affinities can vary between bisphosphonates. In vitro assays have shown zoledronic acid (ZA) has a strong affinity for bone mineral (Lawson et al, 2010). The development of strategies that take into account bone resorption and take advantage of the anti-resorptive properties of bisphosphonates as well as their capacity to bind with high affinity to hydroxyapatite (HA) are a natural evolution for bone tissue engineering carriers.…”
mentioning
confidence: 99%
“…Степень связи различных БФ с гидроксиапатитом и фарнезилпиро-фосфатсинтазой отличается, что, по мнению некоторых ис-следователей [6][7][8], создает предпосылки для различий в эффективности и безопасности препаратов.…”
Section: бфunclassified